Evaluating solid sorbents for CO2 capture: linking material properties and process efficiency via adsorption performance - Saenz Cavazos, Paola A.; Hunter-Sellars, Elwin; Iacomi, Paul; McIntyre, Sean R.; Danaci, David; Williams, Daryl R. (Frontiers in Energy Research, 2023)
Expanding populations and growing economies result in higher energy needs. Meeting this increasing demand, while lowering carbon emissions, calls for a broad energy mix and commercial deployment of solutions like carbon capture and carbon removal technologies. The scale-up of these solutions is partially hindered by the lack of materials-related information, particularly in the case of solid adsorption-based carbon capture technologies. Furthermore, experimental measurement parameters used and how data is presented lack uniformity, which makes material comparisons extremely difficult. This review examines the current state of solid sorbent characterization for carbon capture, exploring physical and chemical properties, performance parameters, and process indicators. Adsorbent performance parameters demonstrate to be the crucial link between intrinsic material properties and the overall adsorption process effectiveness and therefore are the focus of this work. This paper outlines the relevant techniques used to measure Key Performance Indicators (KPIs) related to adsorption performance such as CO2 adsorption capacity, selectivity, kinetics, ease of regeneration, stability, adsorbent cost, and environmental impact. Additionally, this study highlights the relevant experimental conditions for diluted versus concentrated CO2 streams. Lastly, efforts in harmonizing experimental data sets are considered, and an outlook on solid sorbent characterization for carbon capture processes is presented. Overall, the aim of this work is to provide the reader a critical understanding of KPIs from atomic to process scale, highlighting the importance of experimental data throughout.